Effect of Tillage on Physical Properties of Young ALLuviam and Residual Root Volume after Winter Maize (Zea Mays L.) - Singh, Abdhesh K; Singh, S S; Khan, A R; Singh, J P (Journal of Agricultural Engineering, 2006)
A series of experiments were conducted for two consecutive winter seasons at Rajendra Agricultural University, Pusa, India on loamy sand soil having pH 8.8, O.C.- 0.38%, E.C. - 0.26 dsm?¹, bulk density 1.45 Mgm?³, available N 225.7 kg ha?¹, available P2O5 12.1 kg ha?¹ and available K2 87.71 kg ha?¹. The experiment was designed in split-split plot with the treatments of tillage (main), irrigation (sub) and nitrogen (sub-sub plot) having three levels each with three replication under late (28th November) and timely (06th November) sown conditions. Among the treatments only tillage caused significant variation in physical properties manifested through reduction in bulk density from 1.41 to 1.30 Mgm?³, penetration resistance from 2.94 to 2.11 Mpa, mean weight diameter from 6.97 to 5.68 mm with subsequent increase in water stable aggregate from 6.76 to 10.37 per cent and infiltration rate from 0.218 to 0.512 cmh?¹ .The Mould Board plough caused higher root volume (35.30 and 40.38 cc) under late and timely sown, respectively.